Incidental Eosinophilic Chromophobe Renal Cell Carcinoma in Renal Allograft - Abdullah Alharbi; Maram S. Al Turki; Noura Aloudah; Khaled O. Alsaad (Case Reports in Transplantation)
The incidence of renal cell carcinoma (RCC) in renal allograft in transplant recipients is 0.22–0.25%. De novo clear cell, papillary, and chromophobe RCCs and RCCs with sarcomatoid differentiation originating in renal allograft have been reported. Routine surveillance for graft tumours is not routinely practiced and these tumours are commonly asymptomatic and incidentally discovered. We describe a case of incidental, eosinophilic chromophobe RCC in a 31-year-old, long-term renal transplant male recipient, who presented with acute gastroenteritis 11 years after transplantation. The graft was nonfunctional at the time of presentation. Abdominal ultrasound and computed tomography scan demonstrated 1.8 cm well-defined, round enhancing lesion, confined to the renal allograft and suspicious for malignancy. Pathological examination of graft nephrectomy specimen showed gross, histopathological, and immunohistochemical features of eosinophilic chromophobe RCC. Fifty-five months after surgery, the patient was alive and free of malignancy. To the best of our knowledge, only five chromophobe RCCs originating in a renal allograft were previously described in English literature. We suggest that chromophobe RCC should be considered in the differential diagnosis of renal allograft mass, including eosinophilic tumours, and emphasise the importance of periodic screening of renal allograft in all renal transplant recipients.